Fenomena Kecanduan Tiktok dan Dampaknya terhadap Kebiasaan Belajar Siswa Sekolah Dasar - Santi HS; Selvi Anita Sari; Mega Adyna Movitaria; Sunarti Sunarti (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
Digital transformation has introduced the TikTok addiction phenomenon into elementary schools, triggering behavioral and cognitive disruptions among students. The urgency of this study is based on findings of internal noise and intrusive behaviors that hinder the knowledge transfer process in the classroom. This study aims to analyze the manifestations of TikTok addiction and its impact on students' learning habits. This qualitative research employed a case study design. Data were collected through passive participant observation, in-depth interviews with 2 teachers and 5 students, and documentation studies. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Findings indicate that TikTok addiction manifests as: (1) Concentration disorders due to the dominance of viral content such as "Tabola Bale" songs and "velocity" movements in students' minds; (2) Physical fatigue and acute procrastination leading to the loss of study time at home; and (3) Early social imitation through symbols like "black bracelets" indicating age-inappropriate adult behavior. The root cause was identified as personal gadget access starting from preschool age (Kindergarten). TikTok addiction fundamentally undermines students' learning habituation. The implication is that a collaborative strategy between schools and parents is necessary to strengthen digital literacy from an early age to mitigate the negative impacts of technology.